AFIKS DALAM BAHASA DAYAK JANGKANG KECAMATAN JANGKANG KABUPATEN SANGGAU - R. Suhendro; Paternus Hanye; Patriantoro Patriantoro (Universitas Tanjungpura, 2019)
AbstractThis research aimed to describe affix in the Dayak Jangkang language which includes its form, meaning and function. The method used in this research was descriptive method with qualitative form. Source of the data in this study is the Jangkang Dayak language speakers in Jangkang Benua Village, Jangkang District, Sanggau Regency. The data in this study were words that contain affixes spoken by Jangkang Dayak speakers. The techniques used in this study are SLC, SBLC, CS, and fishing techniques. Based on the results of data analysis on the Jangang Dayak language, it can be concluded that there are five affix forms, namely (bo-),(N-), (le-), and (so-) . The five forms of affixes have their own meaning, affix (bo-) means to have or have, to do something or to do something, to obtain or produce something, to be in a state as mentioned in the basic form, reasoned or reciprocal. Affix (N-) has the meaning of doing something an action or action, doing an action, using or working with what is contained in the basic form, producing or making a thing, making or producing what is said in the basic words. Affix (le-) means stating a passive action. Affix (so-) means stating a passive action. The affix function in the Jangkang Dayak language consists of two, namely derivative functions and inflective functions. Keywords: Affix, Derivative, Inflective, Morphology